Overload of anxiety on postural control impairments in chronic stroke survivors: The role of external focus and cognitive task on the automaticity of postural control. - Zahra Ghorbanpour (Public Library of Science (PLoS), 2021)
Background Despite the high prevalence of anxiety among chronic stroke survivors and evidence of its negative effects on postural control in healthy subjects, it is unclear whether anxiety also affects postural control in these patients. Recent evidence of improved postural control of healthy subjects by distracting the attention using an external focus (EF) or cognitive task, raises the question of whether similar benefits would be observed in stroke survivors. Thus, the current study aimed to investigate the effects of anxiety and distracting the attention on postural control of chronic stroke survivors in terms of both postural sway measures and neuromuscular regulation. Methods Postural sway measures and ankle muscle activity of chronic stroke survivors with the high and low level of anxiety (HA-stroke (n = 17), and LA-stroke (n = 17), respectively) and age-, sex-, height-, and weight-matched healthy subjects (n = 17) were assessed while standing on rigid and foam surfaces under following conditions: baseline, internal focus (IF), EF, simple and hard cognitive tasks (SC and HC, respectively). Results Stroke survivors, particularly HA-stroke participants, showed greater postural sway measures (i.e. postural instability) and enhanced co-contraction of ankle muscles (i.e. stiffening of the neuromuscular system) compared with healthy subjects. As opposed to baseline and IF conditions, postural instability and neuromuscular stiffening significantly reduced in EF condition and decreased more in cognitive task conditions, particularly HC condition. Conclusions The results suggest that anxiety enhances stroke-induced postural instability promoting improper neuromuscular control of posture with stiffening strategy, which can be alleviated by EF and cognitive tasks.